Motivational interventions - Karabenick, Stuart A.; Urdan, Timothy C. (Bingley, U.K. : Emerald, 2014)
Researchers from a variety of disciplines are designing creative ways to apply basic research principles to solve persistent motivational problems in education. From brief interventions based on social psychological principles to multi-year collaborative projects with teachers, each of the chapters in this volume describes theory-driven projects that produce genuine benefits for students and teachers. As these and other intervention efforts gain attention, replication, and variation, new questions have begun to emerge. Can these interventions be 'scaled up" to benefit a larger number of students? Will some lose power as they lose novelty? How will these interventions work with other innovations and changes in education? How well will interventions that have been found effective with some populations generalize to other students? These interventions work best when they are targeted to a specific group at a specific point in their educational careers. So questions about scalability and generalizability are empirical questions that will certainly be examined in years to come. By compiling research on motivational interventions we hope that this volume will move this process forward.
Attribution-based treatment interventions in some achievement settings / Raymond P. Perry ... [et al.] -- Intervening to improve children's reading motivation and comprehension : concept oriented reading instruction / Allan Wigfield ... [et al.] -- Harnessing values to promote motivation in education / Judith M. Harackiewicz ... [et al.] -- Going beyond the "Whoa! That's cool!" of inquiry : achieving science interest and learning with the ICAN intervention / K. Ann Renninger ... [et al.] -- Motivating students by "personalizing" learning around individual interests : a consideration of theory, design, and implementation issues / Candace Walkington, Matthew L. Bernacki -- Fostering positive narratives : social-psychological interventions to maximize motivation in the classroom and beyond / Arielle Silverman, Geoffrey Cohen -- Identity-based motivation : core processes and intervention examples / Daphna Oyserman -- Design-based interventions for promoting students' identity exploration within the school curriculum / Avi Kaplan, Mirit Sinai, Hanoch Flum -- An intervention-based program of research on teachers' motivating styles / Johnmarshall Reeve, Sung Hyeon Cheon -- Theory-based interventions with middle school teachers to support student motivation and engagement / Julianne C. Turner -- The emergence of mindfulness-based interventions in educational settings / Robert W. Roeser.
Print version record
Keywords: Education -- General; Education; Motivation in education